Sınav Salonunda Geçen Zaman ve Öğrencilerin Sınav Puanları: Güney Afrika'daki Mesleki ve Teknik Eğitim ve Öğretim Kolejinde Bir Analiz - Amponsah, Samuel (Fırat University, 2017)
Özet: Sınav, öğrencinin bilgi, beceri ve yeteneğini ölçmek için yapılan bir değerlendirmedir. Öğrencilerin performanslarını belirlemek için verdikleri değerlendirme şekli ne olursa olsun, öğrencilere sınav salonunda geçirecekleri belirli bir zaman verilir. Değerlendirmelerini tamamlayan ve değerlendirildikten sonra aynı puanı veya skoru alan öğrencilerin aynı zamanı harcama ihtimalleri çok düşüktür. Öğrencilerin sınav puanlarını etkileyen; ders içeriği, öğretimde kullanılan stratejiler, sınav koşulları ve öğrencilerin sınavlara hazırlıkları gibi bazı faktörler vardır. Bu çalışmada, araştırmacılar, öğrencilerin sınav sorularını cevaplamada geçirdikleri süre ile bunların performansları arasındaki ilişkiyi araştırmaya çalışmışlardır. Bu çalışmanın katılımcıları basit tesadüfi örneklem tekniği ile seçilmiştir. Kaza sonucu örnekleme tekniği ile, ilk dönem sınavlarının sonunda değerlendirilen dört dersin her birinde sınav senaryosuna giren ilk ve son on öğrenciden veri toplanmıştır. Bu araştırmada seksen öğrenciye ait veriler toplanmaya çalışılmıştır. Araştırmanın seksen katılımcısından veri toplamak için açık uçlu bir anket kullanılmıştır. Araştırmanın bulgularına göre, adayların cinsiyeti ile sınav puanları arasında pozitif, fakat anlamlı olmayan bir ilişki ortaya çıkmıştır. Çalışma sonucunda, sınav ve cinsiyette harcanan zamanın öğrencilerin akademik performansı üzerinde önemli bir pratik etkisi olmadığı sonucuna varılmıştır.

Abstract: Examination is an assessment intended to measure student’s knowledge, skills and ability. Irrespective of the form of assessment administered to students to ascertain their performance, students are given a specific time to be spent in the examination hall. Students are highly unlikely to spend the same amount of time finishing their assessments and scoring the same point or mark after they have been assessed. There are some factors that influence student’s examination scores which include the content of courses, strategies used in teaching, examination conditions and students’ preparation towards examinations. In this paper, the researchers sought to investigate the relationship between the duration students spent in answering examination questions and their respective performance. Participants of this study were selected by means of simple random and accidental random techniques. A close-ended questionnaire was used to collect data from the eighty respondents of the study. The questionnaire sought information on starting time for the examinations, finishing time, duration, participants’ gender, age, time of submission of examination script and the duration spent on each paper. Further findings revealed that a positive but non-significant relationship exists between the sex of the candidates and their examination scores. The study concluded that time spent in examination and gender did not have any significant practical effect on students’ academic performance. The authors recommended that educational trainers and facilitators should encourage students to prepare well in advance before taking part in examinations
Time Spent in Examination Hall and Students’ Examination Scores: Analysis from a Technical Vocational Education and Training College in South Africa